Are the changes in observed functioning after multi-disciplinary rehabilitation of patients with fibromyalgia associated with changes in pain self-efficacy?. Issue 17 (14th August 2017) - Rasmussen, Marianne Uggen; Amris, Kirstine; Rydahl-Hansen, Susan; Danneskiold-Samsoe, Bente; Mortensen, Erik Lykke; Christensen, Robin; H. Sjölund, Bengt
Abstract: Objective: To examine the hypothesis that change in pain self-efficacy is associated with observed and self-reported activity, pain intensity, catastrophizing, and quality of life after multi-disciplinary rehabilitation of fibromyalgia patients. Design: In-depth analyses of secondary outcomes of a randomized-controlled trial. Subjects: Women ( N = 187) with fibromyalgia. Methods: Outcomes were Pain Self-Efficacy, Assessment of Motor and Process Skills (AMPS), SF-36 Physical Function (SF-36-PF), pain intensity, and SF-36 Mental Composite Score (SF-36-MCS) to assess quality of life and pain catastrophizing. Individual and group associations between outcomes were examined. Results: Individual changes in pain self-efficacy were not associated with changes in observed activity: AMPS motor ( rs = 0.08, p = 0.27) and process ( rs = 0.12, p = 0.11), not even in those patients with a clinically relevant improvement in observed functioning (38.5%), and only weakly or moderatly with changes in SF-36-PF; ( rs = 0.31, p < 0.0001), SF-36-MSC; ( rs = 0.41, p < 0.0001), and pain catastrophizing ( rs = −0.31, p < 0.0001). No differences in pain self-efficacy were observed between the rehabilitated group and controls (difference: 1.61; 95% CI: −0.84 to 4.06; p = 0.24). However, a subgroup (34%) had a clinically relevant improvement in pain self-efficacy. This group was younger (mean age 41.4 vs. 45.8, p = 0.01), more recently diagnosed (1.8 vs. 2.8 years, p = 0.003), but had an unresolved welfare situation (59% vs. 40%, p = 0.02). Conclusion: The main hypothesis was falsified, as there was no association between pain self-efficacy and actual performance of activity. The relation to functioning may be limited to perceived, cognitive-emotional aspects, as indicated by the weak to moderate correlations to the self-reported measures. Implications for Rehabilitation: Improvement in observed activity post multi-disciplinary rehabilitation was not associated with change in pain self-efficacy. Patients performed better after rehabilitation, but did not perceive to have improved their capacity. The relationship between pain self-efficacy and functioning may be limited to cognitive-emotional aspects rather than actual activity. Both observational and self-reported measures should be included in evaluating outcomes of rehabilitation for patients with fibromyalgia.